Adapting to Industry 4.0 in France: Essential Competencies for a Future-Ready Workforce - Cristina Rodrigues Piazer Turcato; Bruno Pedroso; Maik Arnold; Claudia Tania Picinin (Administrative Sciences)
This paper identifies skills required for workers in Industry 4.0 in France and provides insights to guide the development of a future research agenda. The research draws on a bibliometric analysis of 80 papers, mapping the technical and interpersonal skills needed for professionals to adapt and thrive in the evolving industrial landscape. The results highlight the importance of a multidisciplinary approach integrating competences in information technology, automation, robotics, artificial intelligence, data analysis, project management, interpersonal skills, adaptability, and collaboration. This holistic approach to skills development reveals six major domains: Technical, Flexibility, Inter-Agency, Soft Skills, Innovation, and Information Technology. The conclusions emphasize that the interconnection between these domains is essential to prepare a workforce capable of meeting the challenges and seizing the opportunities of Industry 4.0 in France. The research shows that there is a need for a multidisciplinary and integrated approach that combines technical and interpersonal skills in Industry 4.0 activities. It provides a solid foundation for formulating talent development strategies and educational curricula aligned with the demands of Industry 4.0. By proposing a future research agenda, this study not only highlights key areas for further exploration—economic impact, public innovation policies, and curriculum adaptation—but also contributes to the evolution of human resources in the digital transformation era.